y+x(lnx-lny-1)=0

Simple and best practice solution for y+x(lnx-lny-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+x(lnx-lny-1)=0 equation:


Simplifying
y + x(lnx + -1lny + -1) = 0

Reorder the terms:
y + x(-1 + lnx + -1lny) = 0
y + (-1 * x + lnx * x + -1lny * x) = 0

Reorder the terms:
y + (-1lnxy + lnx2 + -1x) = 0
y + (-1lnxy + lnx2 + -1x) = 0

Reorder the terms:
-1lnxy + lnx2 + -1x + y = 0

Solving
-1lnxy + lnx2 + -1x + y = 0

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add 'x' to each side of the equation.
-1lnxy + lnx2 + -1x + x + y = 0 + x

Combine like terms: -1x + x = 0
-1lnxy + lnx2 + 0 + y = 0 + x
-1lnxy + lnx2 + y = 0 + x
Remove the zero:
-1lnxy + lnx2 + y = x

Add '-1y' to each side of the equation.
-1lnxy + lnx2 + y + -1y = x + -1y

Combine like terms: y + -1y = 0
-1lnxy + lnx2 + 0 = x + -1y
-1lnxy + lnx2 = x + -1y

Reorder the terms:
-1lnxy + lnx2 + -1x + y = x + -1x + -1y + y

Combine like terms: x + -1x = 0
-1lnxy + lnx2 + -1x + y = 0 + -1y + y
-1lnxy + lnx2 + -1x + y = -1y + y

Combine like terms: -1y + y = 0
-1lnxy + lnx2 + -1x + y = 0

The solution to this equation could not be determined.

See similar equations:

| x+0.2x=48 | | 2080x+250(1.5x)=81084 | | 2(a+b)=10 | | 1cm*(1cm/sec)2/1cm | | -16=-4m+5 | | 2x+2y+2z-12=3x+y+z-10 | | .005x=25.5 | | 1xb=5 | | 0.05x=25.5 | | 17x^2-92x-300=0 | | 2d-6d=16 | | f(x)=(-3)x+15 | | 9x^2+24x+6=0 | | 9p*30=674 | | 8n-5+2n=0 | | Y=1/4(x-4) | | 4x/6=1 | | 16x^2+4y^2+96x+10y+100=0 | | Z=x+2y | | Z-x=2y | | x+1=12x+4 | | (4*4)+5m=4 | | y=log(8x) | | =86.010*LOG(28-15)-70.041*LOG(70)+36.76 | | 0.05(c*8)+0.07c=9400 | | 0.05(y*8)+0.07y=9400 | | 1/8=to | | 7(10a+3b)= | | -1/8*-1/3 | | Y+4=(x-1) | | (4y+7)(6+y)=0 | | (4-(-2))/(4-1) |

Equations solver categories